The Oxford Children's Book of Famous People - Oxford University Press (Oxford University Press : Oxford, 2002)
This guide to the people who matter tells the stories of 1000 women and men whose lives have influenced the course of history, from Gengis Khan to Tony Blair, Aristotle to Stephen Hawking. It is organized alphabetically for easy reference, but there are also chronological and thematic directories.
Keywords: Biography